The Empire of Love - Dawson, W. J. (William James), 1854-1928 (Salt Lake City, UT : Project Gutenberg, 2006)
"The Empire of Love" by W. J. Dawson is a religious and philosophical work written in the early 20th century. The book explores the centrality of love in the life and teachings of Jesus Christ, asserting that love is the fundamental principle of Christianity and the key to understanding the divine. Through thoughtful reflection and poignant exposition, the author emphasizes the need for compassion and selfless love in human relationships. At the start of the book, the author presents a tribute to a person who embodied the teachings of love and compassion during their time in London. Dawson establishes a tone that celebrates the transformative power of love, citing Jesus as the ultimate example of this divine affection. He argues that Jesus is profoundly loved not for his achievements or teachings alone, but for the very essence of who he was$1 (Ba lover of humanity. Dawson critiques the failure of many to grasp the simplicity and profundity of Jesus's message, setting the stage for an exploration of love as the universal solution to the complexities of human existence. (This is an automatically generated summary.)s
The genius to be loved -- What is Christianity? -- The justice of Jesus -- Love is justice -- Love and forgiveness -- The practice of love -- Love and judgment -- The wisdom of the simple -- The revelations of grief -- A confession -- A lover of men -- The law of compassion -- The empire of love -- The builders of the empire.
Release date is 2006-08-28
Produced by Al Haines
Keywords: Love -- Religious aspects -- Christianity